ANALISIS PERBANDINGAN PARAMETER TRANSFORMASI ANTAR ITRF HASIL HITUNGAN KUADRAT TERKECIL MODEL HELMERT 14-PARAMETER DENGAN PARAMETER STANDAR IERS - Romi Fadly; Citra Dewi (UNIVERSITAS LAMPUNG, 2014)
This research aims to compare the 14 transformation parameters between ITRF from computation result using the Helmert 14-parameter models with IERS standard parameters. The transforma- tion parameters are calculated from the coordinates and velocities of ITRF05 to ITRF00 epoch 2000.00, and from ITRF08 to ITRF05 epoch 2005.00 for respectively transformation models. The transformation parameters are compared to the IERS standard parameters, then tested the signifi- cance of the differences. The transformation parameters are used to reversly transform to obtain the common points coordinates ITRF00 and ITRF05 system. The value of 14-parameters are also used to transform the check points coordinates on the ITRF00 and ITRF05 coordinate system. The results show that the RMSe difference of the coordinates of the reverse transformation result with Helmert model using computed transformation parameters and the IERS standar parameters are 0.1 mm (for ITRF00) and 0.8 mm (for ITRF05). The results of significance test of 14 parameters to IERS standard parameters are only scale factor (ds) on the transformation from ITRF05 to ITRF00 statistically significant difference. However RMSE values of the coordinate transforma- tion of the check points (Helmert model) using calculated and IERS standar parameters are not difference. It can be concluded that the results of the transformation parameter of 14-parameter Helmert model with the least squares computation is not much different with IERS standard pa- rameters